Investigating electrodes degradation in organic photovoltaics through reverse engineering under accelerated humidity lifetime conditions - Drakonakis, Vasileios M.; Savva, Achilleas; Kokonou, Maria; Choulis, Stelios A. (My University, 2014)
Exposure to accelerated humidity lifetime conditions has been proved to have detrimental effects on organic photovoltaics (OPV) performance, because of the deterioration of the electrodes of the device rather than the active layer. Normal and inverted OPV devices are investigated in order to identify their main degradation mechanisms under accelerated humidity lifetime conditions. Reverse engineering can be a useful technique to probe main degradation mechanisms of the top electrode of both normal and inverted organic photovoltaic (OPVs). By using reverse engineering methods, we show that the major degradation mechanism of inverted OPVs under accelerated humidity lifetime conditions, is due to PEDOT:PSS hole selective top contact.
Keywords: Degradation mechanisms; Electrodes; Humidity lifetime performance; Organic photovoltaics; PEDOT:PSS; Reverse engineering